2013
DOI: 10.1016/j.aprim.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Conocimientos y actitudes de médicos y enfermeras sobre las instrucciones previas

Abstract: The knowledge of physicians and nurses on advance directives is low, so it is necessary to improve this knowledge. Physicians and nurses from both levels show positive attitude towards the use and usefulness and respect the contents of advance directive. The methodology proposed is efficient to implement in a larger study, but should improve the distribution and collection of questionnaires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 6 publications
1
8
0
2
Order By: Relevance
“…Some theoretical (Suess Schwend et al, 2016) and empirical research (Villagrán, Lara Ruiz‐Granados, & González‐Saiz, 2014), as well as a support guide for professionals and users of mental health services (Escuela Andaluza de Salud Pública, 2015), is available in relation to the Comprehensive Mental Health Plan of the Junta de Andalucía , but we found no evidence for its implementation. In addition, previous research in primary, specialist and palliative mental healthcare fields at the national level showed that providers were unaware of what an AHD entails or how to complete one (Aguilar‐Sánchez et al, 2018; Ameneiros, Carballada Rico, & Garrido Sanjuán, 2013; Champer Blasco, Caritg Monfort, & Marquet Palomer, 2010; Fajardo Contreras, Valverde Bolívar, Jiménez Rodríguez, Gómez Calero, & Huertas Hernández, 2015; Nebot, Ortega, Ortega, Mira, & Ortiz, 2010; Toro Flores, Silva Mato, Piga Rivero, & Alfonso Galán, 2013). Thus, considering the international relevance and use of AHDs in clinical practice, it would be useful to collect information about mental health providers’ general knowledge of AHDs and their attitudes towards them before implementing a multistage intervention process in the Spanish context.…”
Section: Introductionmentioning
confidence: 99%
“…Some theoretical (Suess Schwend et al, 2016) and empirical research (Villagrán, Lara Ruiz‐Granados, & González‐Saiz, 2014), as well as a support guide for professionals and users of mental health services (Escuela Andaluza de Salud Pública, 2015), is available in relation to the Comprehensive Mental Health Plan of the Junta de Andalucía , but we found no evidence for its implementation. In addition, previous research in primary, specialist and palliative mental healthcare fields at the national level showed that providers were unaware of what an AHD entails or how to complete one (Aguilar‐Sánchez et al, 2018; Ameneiros, Carballada Rico, & Garrido Sanjuán, 2013; Champer Blasco, Caritg Monfort, & Marquet Palomer, 2010; Fajardo Contreras, Valverde Bolívar, Jiménez Rodríguez, Gómez Calero, & Huertas Hernández, 2015; Nebot, Ortega, Ortega, Mira, & Ortiz, 2010; Toro Flores, Silva Mato, Piga Rivero, & Alfonso Galán, 2013). Thus, considering the international relevance and use of AHDs in clinical practice, it would be useful to collect information about mental health providers’ general knowledge of AHDs and their attitudes towards them before implementing a multistage intervention process in the Spanish context.…”
Section: Introductionmentioning
confidence: 99%
“…Although various studies have shown a positive attitude of providers towards users’ AHD, this does not necessarily translate into providers’ adherence to users’ AHD (Coleman, ). Similarly, Spanish healthcare professionals in the specialist, primary and palliative fields show a positive attitude towards users’ AHD but are unaware of what an AHD comprises or how to complete one (Aguilar‐Sánchez et al, ; Champer Blasco, Caritg Monfort, & Marquet Palomer, ; Fajardo, Valverde Bolívar, Jiménez Rodríguez, Gómez Calero, & Huertas Hernández, ; Toro, Silva Mato, Piga Rivero, & Alfonso Galán, ). Furthermore, no study has explored the viewpoint of Spanish mental healthcare professionals towards AHDs in the mental health field.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies have pointed to a lack of knowledge regarding living wills among health professionals, as opposed to positive attitudes towards the document [16][17][18][19] , with a direct relationship between the level of knowledge and characteristics such as previous experience and academic education 18,19 . Likewise, procedures that do not comply with end-oflife legislation have already been associated with a lack of familiarity with these legal principles 20 .…”
Section: Discussion Of Resultsmentioning
confidence: 99%